Novel radionuclides for use in Nuclear Medicine in Europe: where do we stand and where do we go? - Maija Radzina; Laura Saule; Edgars Mamis; Ulli Koester; Thomas Elias Cocolios; Elina Pajuste; Marika Kalnina; Kristaps Palskis; Zoe Sawitzki; Zeynep Talip; Mikael Jensen; Charlotte Duchemin; et al. (SpringerOpen, 2023)
Abstract Background In order to support the ongoing research across Europe to facilitate access to novel radionuclides, the PRISMAP consortium (European medical radionuclides programme) was established to offer the broadest catalog of non-conventional radionuclides for medical and translational research. The aim of this article is to introduce readers with current status of novel radionuclides in Europe. Main body A consortium questionnaire was disseminated through the PRISMAP consortium and user community, professional associations and preclinical/clinical end users in Europe and the current status of clinical end-users in nuclear medicine were identified. A total of 40 preclinical/clinical users institutions took part in the survey. Clinical end users currently use the following radionuclides in their studies: 177Lu, 68 Ga, 111In, 90Y, other alpha emitters, 225Ac, 64Cu and Terbium isotopes. Radionuclides that would be of interest for users within the next 2-5 years are 64Cu, Terbium radionuclide "family" and alpha emitters, such as 225Ac. Conclusions Thanks to a questionnaire distributed by the PRISMAP consortium, the current status and needs of clinical end-users in nuclear medicine were identified.